La harina de camarón como pigmentante en pollos parrilleros - Inga Ríos, Natali Fabiola (2009)
The work was carried out at the premises of the Experimental Farm "Santa Inés", Technical University of Machala, El Oro Province (altitude 5 m.s.n.m.). The objectives of this research were: To assess the effect of shrimp meal as pigmentante the skin of broiler chickens in the food ration, using the colorimetric DSM; variables measuring food consumption, weight gain and feed conversion. We used the completely randomized design with 5 treatments and 3 replications. 150 chicks were used for 1 days of age were distributed evenly 15 small shed 1 x 1.5 m each to 42 days old. Groups of 10 chickens were each. The treatments used were the witness, 1, 2, 3, 4% shrimp meal. To measure the skin in the last week the range was used DSM calorimeter was measured on all birds and then averaged. To measure the variables of food consumption, weight gain and feed conversion were weight weekly until the birds finish the test, the results reached the following conclusions: The highest percentage of pigmentation was obtained in the group that was treated with 3 and 4 % of shrimp meal. The group that consumed less food, was the group with 1% of shrimp meal. The group that was the best weight was the witness group, followed by the group with 3 % of shrimp meal. The greatest utility was reached with the witness group ($ 57.10), followed by the group with 3% of shrimp meal ($53.30). The mortality rate higher was 2 %.